The Impact of Sustainability and symbolism of Formation in museums - Mohamed Seif Elnasr Ahmed (JES: Journal of Engineering Sciences, 2023)
The museum is a building with a distinctive visual mass, which must have its own symbolism that expresses society and content, In addition, the museum must take into account the global trend in applying sustainability standards. In this research, the question is about the possibility of achieving an evaluation model that can be made to measure the impact of applying environmental sustainability and symbolism of formation in museums. Three steps were taken to discuss this question:The first step was to identify the elements and characteristics of formation in museums, the principles of environmental sustainability, then the types and elements of symbolism.The second step was to study the effect of sustainability and symbolism on the elements of formation in museums.From the previous two steps, an evaluation model was proposed to measure the impact of applying environmental sustainability and symbolism of formation in museums.The third step was to test the evaluation model by using it to analyze some international museum samples that have obtained a certificate from one of the global sustainability systems. Finally, the research has proven that an evaluation model can be made to measure the impact of environmental sustainability and symbolism of formation in museums.